Pergeseran Sistem Sapaan dalam Bahasa Jawa di Desa Sungai Pasir Putih Kecamatan Kelayang Kabupaten Indragiri Hulu - Yulis, Dearby Wandira; Febria, Rhani (UIR Press, 2024)
This research describes the shift in the Javanese greeting system in Sungai Pasir Putih Village, Kelayang District, Indragiri Hulu Regency and the factors that caused the shift. The aim of this research is to describe, analyze and interpret the shift in the system of kinship and non-kinship greetings in Javanese in Sungai Pasir Putih Village, Kelayang District, Indragiri Hulu Regency and the factors that influenced the shift. The theory used in this research is Fishman (2010). The method used in this research is qualitative description. Data collection techniques in this research are observation, interviews and documentation. The results of this research are that there are 17 shifts in the kinship greeting system, consisting of 10 shifts in greetings in kinship relationships and 7 shifts in greetings in marital relationships. Furthermore, 14 data on shifts in non-kinship greeting systems were found, consisting of 8 shifts in general public greetings, 3 shifts in traditional greetings, and 3 shifts in religious greetings. Factors that influence the shift are the existence of a new language, the economy, and marriage.